Corrosion and tribo-corrosion behaviors of nano-lamellar Ni1.5CrCoFe0.5Mo0.1Nbx eutectic high-entropy alloy coatings: The role of dual-phase microstructure. (June 2022) - Wen, Xin; Cui, Xiufang; Jin, Guo; Liu, Yufei; Zhang, Ye; Zhang, Xuerun; Liu, Erbao; Tian, Haoliang; Fang, Yongchao
Abstract: In this work, the effect of the dual-phase microstructure (FCC and Laves phases) of Ni1.5 CrCoFe0.5 Mo0.1 Nbx (x = 0.55 hypoeutectic, 0.68 eutectic and 0.8 hypereutectic) high-entropy alloy coatings on their corrosion and tribo-corrosion behaviors were studied. In a 3.5 wt.% NaCl solution, the FCC phase behaved as anodic sites. With the increase of Nb content, the passive regions of the coatings increased slightly. Mott–Schottky analysis revealed that the improvement in the performance of the passive film is mainly attributed to the reduced point-defect density. The increased Laves phase changed the wear mechanism of the coatings from adhesive to abrasive wear. Graphical Abstract: ga1 Highlights: The effect of the dual-phase microstructure on the tribo-corrosion behaviors of the eutectic HEA coatings was studied. The interaction between FCC and Laves phases in the coatings was revealed by EBSD. Nb0.68 and Nb0.8 coatings exhibited nano-scale pitting sizes. With the increase of Laves phase, the protective capability of the passive films on the coatings was improved.